Analysis of the Methodology of Introduction Into the Educational Process of Modern Technical Measuring Equipment Used in Production, as Well as Caliper Nutrometry and Measurement Methods - Dilshodbek qizi, Karimova Madinabonu; Oybek qizi, Turg’unboyeva Maftuna; Uzaqovich, To’rayev Muhammadjon (European Journal of Life Safety and Stability (2660-9630), 2021)
Methods and means of mass measurement in agriculture are of paramount importance. The accuracy of the measurement method is estimated by its error, and the presence of an error leads to significant losses during control. For example, grain weighing during harvesting is carried out on stationary automobile scales. Periodic verification of such scales is carried out at the place of their installation. The measurement error on the certified scales does not exceed one percent, but taking into account the fact that the scales are installed outdoors, they become dirty, corrode, and sometimes the weighing method is not followed. As a result, the measurement error increases significantly.